Effects of growth temperature on exciton lifetime and structural properties of ZnO films on sapphire substrate - Cho, S.; Kim, S. I.; Kim, Y. H.; Mickevicius, J.; Tamulaitis, G.; Shur, M. S. (WILEY-V C H VERLAG GMBH, 2006)
We report on optimization of growth conditions by studying the structural and optical properties of ZnO films grown on sapphire substrate by pulsed laser deposition at different growth temperatures. The crystallographic structure and surface morphology were studied by X-ray diffraction and atomic force microscopy, respectively. The flattest surface was observed in the sample grown at substrate temperature of 500 degrees C. The optical characterization was performed by steady state and time resolved photoluminescence spectroscopy. Photoluminescence of the samples was studied at low CW excitation and at high-power-density pulsed excitation in picosecond domain. Stimulated emission was observed at pulsed excitation. Carrier lifetimes were found to significantly depend on the growth temperature reaching the peak value also in the samples grown at approximately 500 degrees C. (c) 2006 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.
Keywords: PHOTOLUMINESCENCE LIFETIME; SPECTRA; EPITAXY; BULK